Investigation of curcumin analogs by molecular docking,md simulation and MM-PBSA calculation as potzential GSK3-β protein inhibitor to treat wounds - Forid, Md Shaekh; Roney, Miah; A. K. M., Moyeenul Huq; Md. Nazim, Uddin; Mohd Hamzah, Mohd Nasir; Mohd Fadhlizil Fasihi, Mohd Aluwi; Muhammad Saupi, Azuri; Wan Maznah, Wan Ishak (AMG Transcend Association, 2025)
Wound healing is associated with many proteins, among them GSK3-β, which is crucial for cutaneous wound healing. However, no particular treatment option is available to target this protein. Therefore, researchers are actively involved in the urgent development of new wound healing agents that are more effective against the GSK3-β protein. This study aims to identify and forecast potential curcumin analogs to inhibit GSK3-β protein function using an in-silico approach. A series of computational approaches, such as ADMET, molecular docking, molecular dynamics simulation, and MM-PBSA. Eight curcumin analogs were identified using the Swiss similarity score. Then, four potential compounds were screened using Druglikeness and ADMET-based assay. Consequently, molecular docking results showed that CHEBI3962 (-40.9219 kcal/mol) and CHEBI65737 (-35.5336 kcal/mol) bound with the lowest interaction energy compared to the co-crystalized ligand (-29.1169 kcal/mol). Furthermore, molecular dynamics simulation revealed that CHEBI65737 is more stable at the active site of GSK3-β. Additionally, MM-PBSA results confirmed that CHEBI65737 (-21.51±4.24 kcal/mol) has the highest binding affinity compared to CHEBI3962 (-15.01±3.99 kcal/mol) and the cocrystalized ligand (-17.49±3.70 kcal/mol). Hence, curcumin analogue CHEBI65737 presents as a promising candidate for further investigation and development as a GSK3-β inhibitor.